2005
DOI: 10.1021/cm050763r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Phosphorescence Appropriate for the Long-Lasting Phosphors Eu2+-Doped SrAl2O4 with Codopants Dy3+ and B3+

Abstract: The existing mechanisms proposed to explain the phosphorescence of SrAl2O4:Eu2+,Dy3+ and related phosphors were found to be inconsistent with a number of important experimental and theoretical observations. We formulated a new mechanism of phosphorescence on the basis of the facts that the d orbitals of Eu2+ are located near the conduction band bottom of SrAl2O4, that the Eu2+ concentration decreases during UV excitation, and that trace amounts of Eu3+ are always present in these phosphors. In our mechanism, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
434
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 670 publications
(472 citation statements)
references
References 65 publications
19
434
2
3
Order By: Relevance
“…Upon lowering the temperature a second, blue, emission band becomes visible (λ max = 445 nm). Although less well studied as the green emission band, its presence has been reported earlier in several papers [16,17,26]. In the figure, the temperature dependency of both blue and green emission upon excitation with 370 nm is visible.…”
Section: A Photoluminescence Of Sral 2 O 4 :Eudysupporting
confidence: 52%
See 2 more Smart Citations
“…Upon lowering the temperature a second, blue, emission band becomes visible (λ max = 445 nm). Although less well studied as the green emission band, its presence has been reported earlier in several papers [16,17,26]. In the figure, the temperature dependency of both blue and green emission upon excitation with 370 nm is visible.…”
Section: A Photoluminescence Of Sral 2 O 4 :Eudysupporting
confidence: 52%
“…Different coordination for both sites is then expected to sufficiently change the crystal field strength and centroid shift to arrive at the observed spectral differences. Nevertheless, several authors discarded this hypothesis because both sites are seemingly too similar to explain the large energy difference when judging on the emission bands [15,16,18]. As an alternative explanation, Poort et al [26] suggested that the two emission bands result from a possible preferential orientation of the d orbitals of Eu 2+ on Sr sites that appear to line up.…”
Section: Previously Suggested Origins Of Both Emission Bandsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] Until now, persistent luminescence has relied on short-wavelength excitation (e.g., ultraviolet light) which has rather limited tissue-penetration depth. [710] To address this problem, a NIR-light-stimulated PL mechanism was proposed in LiGa 5 O 8 :Cr 3+ , to release energy trapped in deeper energy levels of the phosphor, but in this case, the energy must be precharged by UV-light and the photostimulated emission continues to weaken after each cycle of photostimulation and will finally become extinguished. [3,11] Very recently, the PL phosphor, ZnGa 2 O 4 :Cr 3+ (ZGC), was found to be activatable by using tissue-penetrable red light, which means that energy can be recharged and NIR PL imaging is no longer limited by the luminescence-decay life-time of the phosphor.…”
Section: Introductionmentioning
confidence: 99%
“…To make such NIR-persistent phosphors bulk crystal requires temperatures >750 °C in traditional solid-state annealing reactions. [1,7,13] Moreover, to convert such bulk crystal into nanoparticles that are sufficiently disperse for biological applications, certain tedious physical treatments such as grinding [2,3,14,15] or laser ablation [16] must be utilized. The afforded products are generally highly heterogeneous and suffer from severe agglomeration.…”
Section: Introductionmentioning
confidence: 99%